Application of invasive medical and pharmacological measures by German emergency paramedics - Koch, Sebastian; Herwig, Markus; Kahl, Daniel (Frontiers in Disaster and Emergency Medicine, 2023)
Introduction: German emergency paramedics are to avert serious damage to the patient's health in the event of acute illness or accidents. For this purpose, they have a variety of invasive medical and pharmacological measures at their disposal in addition to their three-year professional training. The aim of this thesis is to investigate the use of invasive medical and pharmacological measures by emergency paramedics in the German rescue service by means of instruments of professional scientific research. In doing so, the motivations of emergency paramedics to refrain from using these measures will be investigated for the first time. Methods: For this study, rescue missions were analyzed during the period July 1, 2022, to June 30, 2023. The chosen method involved a quantitative document analysis of the deployment protocols to investigate the use of invasive and pharmacological measures by emergency paramedics and the reasons against their use. Results: During the period, N = 10,102 (100%) rescue missions could be evaluated. Analysis of the data revealed that invasive medical measures were used by emergency paramedics in n = 1,211 (11.9%) missions and pharmacologic measures were used in n = 1,403 (13.8%) missions. Most frequently, emergency paramedics concluded that invasive medical measures were not required. Discussion: In summary, the use of invasive medical measures is not a standard part of the emergency medical services mission. Rather, the focus is on diagnostics and transport of patients to an appropriate destination hospital. An adjustment of prehospital care structures based on evidence-based data and an update of the catalog of indications for emergency physician interventions would be elementary for this goal. Further studies of professional fields of action in emergency and rescue medicine are necessary in order to analyse and optimise care structures. This would not only allow conclusions to be drawn about the future education, further education and training of rescue service personnel, but also allow care structures to be adapted to the current state of science and the care needs of patients.